THE EFFICIENCY OF ENTERPRISES’ ACTIVITY IN THE MARKET OF LOGISTICS SERVICES IN UKRAINE - Klymenko , V.V.; Lozova , G.M. (The actual problems of regional economy development, 2021)
The article is devoted to the analysis of the efficiency of logistics companies in the market. The aim of the article is to analyze the factors influencing the efficiency of logistics companies based on the study of the logistics services market and study the behavior of leading players in the Ukrainian logistics services market. In the process of research, the authors used a dialectical method, which revealed the essence of the concept "efficiency", conditions and performance indicators of logistics companies; systemic and synergetic approaches, which allowed to consider the evaluation of the efficiency of companies in close connection with ensuring their competitive advantages in the market of logistics services, to analyze the performance indicators for different components of the logistics companies’ activities. The article examines the current state and main trends in the development of the logistics services market in Ukraine. It is noted that in 2021 there is a slow recovery of the logistics services market in the context of the continuation of the COVID-19 pandemic. In the process of analysis, the concept of efficiency of a logistics company is determined, which is revealed in the work through the relevant aspects of its activities. The methodology to assess the integrated economic efficiency of the logistics company is of scientific interest. The ten top logistics companies operating in Ukraine are analyzed in order to determine their competitive advantages and assess market efficiency. The top five logistics companies have been found to be subsidiaries of powerful multinational companies focused on providing integrated logistics solutions. As for the Ukrainian market leaders, they are aimed at finding niche segments, offering their customers unique logistics services. The authors propose a system of indicators by which it is possible to assess the integrated efficiency of logistics companies: indicators of the production component; indicators of the financial component; indicators of the personnel component; indicators of the marketing component; indicators of the management component.